Preparation of S-glycoside surfactants and cysteine thioglycosides using minimally competent Lewis acid catalysis. (3rd March 2016) - Szabó, Lajos Z.; Hanrahan, Dillon J.; Jones, Evan M.; Martin, Erin; Pemberton, Jeanne E.; Polt, Robin
Highlights: Thioglycosides can be readily prepared from per- acetylated carbohydrate donors. S-Glycosylations are catalyzed using the minimally competent Lewis acid InBr3 . Only β anomers are formed. Glycosylation of cysteine and a library of thio-glycolipids are produced by Zemplèn deacylation. Graphical abstract: Abstract: Here we report a method for the preparation of anomerically pure β-S-glycopyranosides (1, 2- trans- glycosides) from the corresponding peracetate donors. S-glycosylation was performed in CHCl3 at reflux in the presence of a catalytic amount of InBr3 . Deacylation of the intermediate peracetates were achieved under Zemplén conditions. Five pyranose examples, monosaccharides D-glucose and D-galactose and disaccharides cellobiose, maltose, and lactose, were used as donors, and five thiols including an α/ω dithiol and Fmoc-L-cysteine were used as acceptors. Melting points, high res MS, [α]D and NMR data ( 1 H and 13 C, including COSY, HSQC and HMBC) are reported for compounds not previously described.